A Novel Molecule in Human Cyclic Endometrium: LncRNA TUNAR Is Involved in Embryo Implantation - Wang, Yuan; Hu, Shuanggang; Yao, Guangxin; Zhu, Qinling; He, Yaqiong; Lu, Yao; Qi, Jia; Xu, Rui; Ding, Ying; Li, Jiaxing; Li, Xinyu; Sun, Yun (Frontiers in Physiology, 2020)
Embryo implantation rate remains an inefficient process in in vitro fertilization and embryo transfer (IVF-ET) cycles. The role long noncoding RNA (lncRNA) plays in embryo implantation remains unclear. We aimed to investigate the expression pattern of lncRNA TCL1 upstream neural differentiation-associated RNA (TUNAR) in human cyclic endometrium and clarify the role of TUNAR in the development of endometrial receptivity. Endometrial biopsies were collected at the late proliferative phase, luteinizing hormone (LH)+2 and LH+7, from patients with or without recurrent implantation failure (RIF). Real-time RT PCR was performed to detect the level of lncRNAs. After pZW1-snoVector-TUNAR transfection, multiple function of TUNAR in endometrial epithelial cells (EECs) and endometrial stromal cells (ESCs) was investigated. The expression of TUNAR in endometrium was found down-regulated at LH+7 and up-regulated in RIF patients. In proliferative phase, TUNAR was overwhelmingly more abundant in ESCs and regulated its proliferation. In LH+7, the difference in the expression of TUNAR between ESCs and EECs was narrowed. Overexpression of TUNAR not only impaired spheroid attachment to EECs, but also inhibited decidualization of ESCs. TUNAR was found expressed in human endometrium for the first time, which might be involved in embryo implantation by modulating the blastocyst attachment to the endometrial epithelium and regulating the proliferation and decidualization of ESCs. Our study helps us to better understand the molecular mechanisms of embryo implantation and may provide a promising biomarker of endometrial receptivity.